The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/bot.0000000000001959
|View full text |Cite
|
Sign up to set email alerts
|

Stability-Based Classification of Ankle Fractures—The Long-Term Outcome After 11–13 Years of Follow-up

Abstract: Objectives: To assess the long-term functional and radiological outcome, as well as complications and reoperations of ankle fracture patients treated based on stability classification.Design: Retrospective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…This was confirmed as all the X-rays showed an anatomical reduction and a fully healed fracture. Most patients, including those in the control group, Zimmermann et al Journal of Orthopaedic Surgery and Research (2024) 19:327 had medial and lateral clear spaces symmetrically smaller than 4 mm, which might be one radiological sign of developing arthritis according to van Dijk and Scranton [18,[50][51][52]. However, no other signs of arthritic changes, such as osteophyte formation, subchondral sclerosis or subchondral cysts, were observed.…”
Section: Discussionmentioning
confidence: 93%
“…This was confirmed as all the X-rays showed an anatomical reduction and a fully healed fracture. Most patients, including those in the control group, Zimmermann et al Journal of Orthopaedic Surgery and Research (2024) 19:327 had medial and lateral clear spaces symmetrically smaller than 4 mm, which might be one radiological sign of developing arthritis according to van Dijk and Scranton [18,[50][51][52]. However, no other signs of arthritic changes, such as osteophyte formation, subchondral sclerosis or subchondral cysts, were observed.…”
Section: Discussionmentioning
confidence: 93%
“…This is one of the longest RCT follow-up of patients with a type 44B1 ankle fracture treated with or without surgery. Karkkola et al 10 reported on similar numbers in their assessment of stable and unstable ankle fractures over a 12-year period; however, this was a retrospective study.…”
Section: Strengths and Limitationsmentioning
confidence: 88%
“…Most patients, including the control group, showed medial and lateral clear spaces symmetrically smaller than 4 mm, which might be one radiological sign of developing arthritis according to van Dijk and Scranton. [15,[46][47][48] However, no signs of arthritic changes such as osteophyte formation, subchondral sclerosis or subchondral cysts were seen.…”
Section: Discussionmentioning
confidence: 99%